249 Targeting IFNβ-regulated secretory profiles to overcome acquired anti-PD-L1 resistance. (9th November 2020) - Shi, Yuhao; Dolan, Melissa; Mastri, Michalis; Eng, Kevin; Ebos, John
Abstract : Background: Therapeutic targeting of programmed cell death protein ligand 1 (PD-L1) has led to durable benefits for many cancer patients; however, the development of acquired resistance is common. Dysregulated type II interferon (IFN) signaling on tumor cells can contribute to resistance via altered expression of IFN stimulated genes (ISGs), which include cytokines and growth factors capable of immune-suppression and tumor promotion. However, the role of type I IFNs, including IFNα and IFNβ, in acquired resistance remain understudied. Here we examined the impact of chronic PD-L1 blockade to evaluate the role of IFN-related secretory changes in preclinical models of resistance. Methods: Using a mouse breast EMT6 orthotopic tumor model, we selected PD-L1 drug resistant (PDR) cells from tumors initially responsive to PD-L1 blockade, but that later relapsed. Using transcriptomic and proteomic approaches, we evaluated secreted proteins associated with IFN signaling. To test for direct connections between PD-L1 and IFN signaling in secretory profile modulation, genetic and therapeutic disruption of PD-L1/IFNAR1 were conducted in vitro. Results: We identified a unique gene signature for secreted proteins following acquired resistance to PD-L1 blockade that associated with IFN signaling. This secretory signature was validated using publicly available datasets derived from preclinical tumors and clinical biopsies after anti-PD-L1 treatment failure. Interestingly, genetic and antibody inhibition of PD-L1 in vitro enhanced PDR secretory signatures following IFNβ stimulation suggesting PD-L1 tumor-intrinsic functions may regulate IFN responses following acquired resistance. To test whether secretory profiles impact tumor growth, inhibition of specific ISGs (IL-6) or ISG regulators (IFNAR1) were examined and found to inhibit PDR tumors in vivo, compared to parental controls. Conclusions: Together, these findings identify a secretory profile associated with acquired resistance to PD-L1 blockade that may be modulated, at least in part, by IFNβ. Selective targeting of secreted ISGs may provide a benefit for patients after anti-PD-L1 treatment failure.